Feasibility of omega bench grafting in guava tree (Psidium guajava L.) propagated via herbaceous stem cutting - Casagrande, Izabella Parkutz [UNESP]; Oliveira, Gabriele da Silva [UNESP]; Leite, Gustavo Walace Pacheco [UNESP]; Teixeira, Gustavo Henrique de Almeida [UNESP] (Taylor & Francis, 2019)
Root-knot nematode Meloidogyne mayaguensis Rammah & Hirschmann is a limiting factor in guava tree (Psidium guajava L.) production around the world. An alternative to address this problem is the use of resistant root-knot nematode rootstocks. However, the guava nursery system which is based on herbaceous stem cutting propagation needs to be modified as a rootstock produced via cutting must be grafted with nematode susceptible commercial cultivars. Thus, the objective of this study was to verify the feasibility of omega bench grafting in guava tree propagated by herbaceous stem cutting. Root-knot nematode tolerant ‘Tailandesa’ herbaceous stem cuttings was used as rootstock and ‘Paluma’ and ‘Pedro Sato’ as commercial cultivar grafts. It was observed 100% rooting, cutting survival, and leaf retention on rootstocks grafted with ‘Paluma’ and ‘Pedro Sato’. However, grafting take was not successful as the tissues presented fast oxidation, dehydration and graft death in both commercial cultivars. However, the immersion of the grafts into a solution containing 2.0% citric acid and 1.0% ascorbic acid controlled the oxidation process and resulted in 28.6% and 37.5% successful grafting in the combinations ‘Paluma’/‘Tailandesa’ and ‘Pedro Sato’/’Tailandesa’, respectively.
Keywords: Meloidogyne mayaguensis Rammah & Hirschmann; Psidium guajavaL; root-knot nematode; Rootstock